Hadith #6804 - Sahih Muslim - Salman Farsi (Sahih Muslim)
Verily, there are one hundred (parts of) mercy for Allah, and it is one part of this mercy by virtue of which there is mutual love between the people and ninety-nine reserved for the Day of Resurrection.
Grade: Sahih